Road Traffic Crash Data Management in ASEAN: 3-5-2 Perspective - Zainal Abidin, A.N.S.; Roslan, A.; Shahril, R.; Jamaludin, A.S.; Muhd Razali, M.N.; Abu Kassim, K.A. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Every year approximately 1.3 million people are killed on roads around the world. Without new and effective actions, deaths in low to middle-income countries are forecasted to rise steeply, as the level of motorization is increasing. The availability of road safety data is fundamental to improving road safety outcomes, tracking progress, and achieving the road safety targets set by each country. With consistent and standardize collection and management, these data will provide beneficial and accurate insights for trends monitoring, future and time series prediction, and ultimately a reliable review of currently implemented programs. However, managing the data is a challenging aspect especially when it involves multiple agencies with different focuses and requirements and countless bureaucracy. By continued adoption of the "3-5-2" concept from football strategies, this paper will review the status-quo conditions of road crash data collection and management in the middle-income tier ASEAN countries. These shall be one of the core values for effective road safety management and improvement stipulated under the Decade of Action for Road Safety.